TANTANGAN IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH - Triatmanto Triatmanto (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Challenges in the Implementation of Character Education at School.This article discusses challenges in character education at school by integrating itinto every lesson. The integrated character education in every lesson in every levelof education can be implemented in the instructional materials, processes, andlearning evaluation. During the implementation, the selection and synchronizationof materials and types of characters to be developed are required in order toprevent the discrepancy or redundancy. In integrated character education, there areinternal and external changes. The former come from the curriculum, mindset,teachers, principal, or even bureaucracy. The latter mainly come from the growthand advance of the information technology which can be directly accessed by thestudents. Due to all of those challenges, two approaches to facing them can betaken. The internal approach can be in the form of improving the understanding ofcharacter education by conducting a training/workshop, sharing ideas with others,and synchronizing the policy in education. The external approach can be adoptedby placing character education experts in the regulation sector and the mass-mediasupervisory board in general.Keywords: character education, implementation, challenges